Smoke control and temperature distribution of tunnel fires under longitudinal ventilation combined with shaft exhaust - Xinyue Zhang; Weiling Ma; Liangliang Tao; Yanhua Zeng; Yumin Wen (Case Studies in Thermal Engineering)
Longitudinal segmental smoke exhaust is often used for fire tunnels longer than 5 km. With the combined effect of longitudinal ventilation in the main tunnel and fan suction in the exhaust shaft, the smoke exhaust path is different from that of a traditional single-tube tunnel. Findings reported in the literature is insufficient to support the rapid development of extra-long road tunnels. In this paper, a numerical model was established by FDS (Fire Dynamics Simulator), and a 1:15 model test platform was built for verification. The effects of different longitudinal velocities, exhaust velocities, bifurcation angles, and exhaust shaft slopes on tunnel fires were analyzed for the longitudinal ventilation combined with shaft exhaust smoke evacuation mode (LVSE). The results show that when the exhaust velocity is greater than 4.5 m/s, increasing the exhaust velocity has a limited effect on reducing the smoke length downstream of the exhaust shaft. The bifurcation angle has a significant effect on the velocity distribution in the ventilation shaft and the main tunnel. When the bifurcation angle is less than 45°, the airflow in the main tunnel is more likely to enter the exhaust shaft, and the velocity in the exhaust shaft is more than 5 m/s. It is more favorable to reduce the smoke length when the slope of the exhaust shaft is not less than 7 %. The high-temperature flue gas collects and forms a vortex near the vent under the LVSE mode, which makes the temperature decay rate slower than that when only longitudinal ventilation is used. The temperature decay model for the LVSE mode is obtained. This study is intended to provide a reference basis for the fire safety design of extra-long road tunnels under the LVSE mode.